Police recruit narratives and publicly oriented vocabularies of motive - Wozniak, Jesse S.G. (International journal of police science & management, 2023)
Although who chooses to become a police officer and why they do so is pivotal for understanding policing, few studies explore recruit motivations. We help to fill this research void through analysis of open-ended narratives penned by police recruits during the academy in a large rust belt city explaining why they want to become police officers, supplemented with qualitative follow-up interviews conducted with randomly selected participants. Of the existing studies on police recruit motivation, nearly all use fixed-response surveys of researcher-selected answers. Despite our respondents being completely free to use their own words, their motivations demonstrate a striking similarity to the findings of previous literature. These stated motivations of altruism and community concern also stand in stark contrast to the public behaviors of police. We suggest this consistency in stated motivations and disconnect with public behavior evinces a publicly oriented vocabulary of motive in which police recruits are attempting to voice the “appropriate” reasons for joining the force.